BACKGROUND OF THE DEGREE IN PUBLIC ACCOUNTING - José G. Vargas Hernández (Universitas Brawijaya, 2012)
Abstract: Background of the Degree in Public Accounting. This paper aims to review public accountant education in terms of the interrelated subjects as well as its background. The results of this education development project improve the formation of the accountant public education because of its linkage between teachers and students in the research process and the design of new teaching strategies that contribute to solving real problems and facilitate the social projection. The academic administration is characterized by processes that arise and is generated within the same individuals, focused on the construction and reconstruction of knowledge, proper training and formation of builders of their own processes. Abstrak: Latar Belakang Pendidikan Akuntansi Publik. Penelitian ini bertujuan untuk mereviu pendidikan akuntan publik dalam hal hubungan antarsubjek serta latar belakangnya. Hasil dari proyek pengembangan pendidikan seperti ini menunjukkan bahwa pembentukan pendidikan akuntan publik dapat diperbaiki karena pengembangan proyek pendidikan menghubungkan guru dan siswa dalam proses penelitian dan desain strategi pembelajaran yang baru yang berkontribusi pada pemecahan masalah serta fasilitasi proyek sosial. Pendidikan administrasi dibentuk dengan proses yang muncul dan dihasilkan oleh individu-individu yang sama, berfokus pada konstruksi dan rekonstruksi pengetahuan, pelatihan yang layak dan pembentuk atas proses mereka sendiri.